Pengaruh Level dan Lama Waktu Fermentasi Tongkol Jagung Menggunakan EM4 terhadap Kandungan Protein Kasar, Lemak Kasar, Kadar Abu, dan Energi: Indonesia - Nelcy Jessika Molo; Gustaf Oematan; Grace Maranatha (Yayasan Sumber Daya Manusia Cerdas, 2023)
This study aims to determine the effect of the level and length of time of fermentation of corn cobs using EM4 on the content of crude protein, crude fat, ash content, and energy. This study used a completely randomized design with 6 treatment factorial patterns with 3 replications. The use of RAL factorial pattern has two factors. The first factor (A) is the EM4 dose which is divided into 3 levels, namely: A1 = 10 ml, A2 = 15 ml, A3 = 20 ml and the second factor (B) is the fermentation time which is divided into 2 levels, namely: B1 = 7 days and B2 = 14 days. The variables studied included crude protein content, crude fat content, ash content and energy. The resulting data were analyzed statistically using analysis of variance with the help of SPSS 21. The average of the analysis results for crude protein content (5.723%), crude fat content (0.753%), ash content (2.722%) and energy (17.039%) showed no interaction (P>0.05) between EM4 level and corncob fermentation time. It was concluded that the use of EM4 solution with different levels in the corn cob fermentation process had no significant effect (P>0.05) on crude protein content, crude fat content, ash content and energy. Fermentation time had no significant effect (P>0.05) on crude protein content, crude fat content and energy but had a significant effect (P<0.05) on ash content.